Is It Possible to Perform Fifth Carpometacarpal Joint Arthroscopy? Cadaveric Study on Its Feasibility, Safety, and Potential Hazards in Portal Creation - Koo, Siu Cheong Jeffrey Justin; Pang, Henry; Ho, Pak Cheong (Journal of Wrist Surgery, 2022)
Background Fifth carpometacarpal joint (CMCJ) fracture dislocation is a relatively rare injury and most will require operative treatment because of its unstable nature. Improper reduction and fixation lead to joint surface destruction, pain, and reduced grasping power. Intra-articular fragment reduction is often obscured by dorsally displaced ulnar fragment. Therefore, fifth CMCJ arthroscopy can be advantageous in assisting intra-articular fragment reduction. However, there is no detailed description of the portal landmarks or portals' relationship with adjacent important structures in the literature.Purposes To explore the feasibility and safety of fifth CMCJ arthroscopy, locations of the portals are examined in cadaveric hand specimens. Their proximity to important anatomical structures such as dorsal cutaneous branch of ulnar nerve (DCBUN), ring finger and little finger extensor digitorum communis (EDC), and extensor digiti minimi (EDM) is measured.Methods Fifth CMCJ arthroscopy is performed on 11 cadaveric hand specimens by specialist-level surgeon. The portals are marked and portal positions are further confirmed under the fluoroscopy. Then the cadaveric specimens were undergone anatomical dissection by specialist-level surgeon. During dissection, the spatial relationship between the portal positions and DCBUN, EDC to ring finger and little finger, and EDM is identified. The distance between the portals and the above important structures was measured in millimeters.Results DCBUN was consistently found between fourth metacarpohamate (4-MH) and fifth metacarpohamate (5-MH) portals, with it being closer to the latter (mean distance, 2.03 mm; range, 0–4.43 mm; standard deviation [SD], 1.09 mm). The closest tendon for 4-MH portal is ring finger EDC (mean distance, 2.65 mm; range, 0–5.89 mm; SD, 1.78 mm), while 5-MH portal and accessory portal were closest to EDC (mean distance, 1.88 mm; range, 0–3.69 mm; SD, 1.25 mm) and EDM (mean distance, 7.79 mm; range, 6.63–10.72 mm; SD, 1.49 mm), respectively. During the process of specimen dissection, we found no damage to the above structures after portal introduction.Conclusion The above findings support the use of fifth CMCJ arthroscopy, which can be used for assisted reduction in fifth metacarpal base fracture dislocation and hamate body fracture. Gentle soft tissue spreading technique during portal creation prevents injury to the important structure surrounding the portals.Level of evidence This is a Level V study.
Keywords: fifth carpometacarpal joint arthroscopy; dorsal cutaneous branch of ulnar nerve; extensor digitorum communis; extensor digiti minimi; cadaveric study